Isolation and Identification of Terpenoids from Artocarpus camansi Leaves Based on Column Chromatography and UV-IR Spectroscopy - Ramadani Ramadani (Universitas Pendidikan Mandalika, 2025)
This study aims to isolate and identify terpenoid compounds from kluwih leaves (Artocarpus camansi). Extraction was done using methanol solvent, followed by n-hexane fractionation, which produced a concentrated blackish green extract. Compounds were separated through column chromatography with silica gel as the stationary phase and n-hexane as the mobile phase, and a mixture of n-hexane: ethyl acetate, producing eight fractions. The third fraction, obtained as green crystals, exhibited a positive reaction to the Liebermann-Burchard reagent, a specific test for the presence of terpenoid compounds. The observed colour change indicated the presence of terpenoids, making this fraction a promising candidate for isolation and detailed analysis. After recrystallisation, white needle-shaped crystals were obtained with a melting point of 141â€“142.8Â°C. Purity testing using thin layer chromatography (TLC) showed a single spot in various eluents, indicating that the isolated compound was pure. Further characterisation using UV spectroscopy showed maximum absorption at 210.2 nm, while IR spectroscopy showed the presence of OH, methyl, and non-conjugated C=C double bonds. Based on these data, the isolated compounds can be identified as terpenoid compounds. This study provides a basis for further studies on the structure and biological activity of kluwih leaves.